Pedestrian perception of façade aesthetics and architectural identity: A case study of New Road, Kathmandu - Katawal, Suragi; Ratna Bajracharya, Ashim (Journal of Innovations in Engineering Education, 2026)
As a part of daily life, people must pass through and visually experience the city environments we live in. The visual appreciation of such urban environments is a product of our perception and cognition. An urban environment is a diverse setting of architecture elements such as buildings, spaces, humans and their inter relationships. A building facade acts as a visual interface between the building and its urban environment. This study aims to explore the pedestrians’ perception of facades aesthetics and architectural identity along two distinct stretches of New Road, Kathmandu: Stretch I (New Road Gate to Juddha Salik) and Stretch II (Juddha Salik to Indrachowk). The research adopts a qualitative data collection method such as interviews and field observation, photo elicitation methods (PEI) and thematic analysis. The findings establish façade perception as a sequential perceptual process, where physical form generates sensory experience that constructs architectural identity. The study offers valuable insights for architects, urban planners, and academics for interpreting buildng facades.